An Analytical Study of the Levels of Administrative Organization among Directors of Sports Activity Departments in Dhi Qar Province from the Perspective of Physical Education Teachers - Abdul Ameer Ali Yousif (Wahid Hasyim University, 2026)
The importance of this research lies in the fact that administrative organization is a key requirement and one of the fundamental pillars for the success of any institution, and the role of these institutions in supplying national teams and age groups with talent. From this perspective, the researcher He will build and standardize an administrative organization scale, and this is where the importance of the research lies. The research problem arose from the researcher's observation of administrative work and his participation in many sporting events at the level of Nasiriyah district In Dhi Qar Governorate, it was found that there was a disparity in the administrative organization of the sports activity department. Therefore, the researcher decided to study this case and find some administrative solutions according to well-studied scientific standards and a specific scale for it The research aims to develop and standardize an administrative organization scale specific to this category of institutions, in order to contribute to regulating and organizing their administrative work and raising the overall level of sports in the district and governorate to the best possible standard An assessment of the administrative organization of sports activity directors in Dhi Qar Governorate from the perspective of physical education teachers, and an identification of the level of administrative organization of sports activity directors in Dhi Qar Governorate From the perspective of physical education teachers, the researcher used the descriptive survey method to suit the nature of the problem and achieve the research objectives. The research population was defined as physical education teachers in the district In Nasiriyah, Dhi Qar Governorate, for the academic year 2022-2023, the number of (240) representing Nasiriyah District and its sub-districts was studied. One of the most important conclusions is that the heads of Dhi Qar clubs possess good levels of administrative organization, according to the members of the administrative bodies.